Endodontic treatment of a large periapical cyst with the aid of antimicrobial photodynamic therapy: Case report - Abu Hasna, Amjad [UNESP]; Henrique Ferrari, Carlos [UNESP]; Talge Carvalho, Cláudio Antonio [UNESP] (Editora Cubo, 2019)
Introduction: Periapical cysts, especially those of great extension, represent a challenge for endodontics, due to the ineffectiveness of traditional root canal treatment (RCT) in such cases. The aim of this case report was to evaluate the effectivity of antimicrobial photodynamic therapy “aPDT” when associated with calcium hydroxide Ca(OH)2 in treating such cysts. Case report: A 40-years-old female patient complained of bulging in the upper anterior region of the mouth. The clinical examination showed an extensive swollen periodontal area, painful with digital palpation, with a negative response to thermal tests on teeth 11 and 21. After traditional RCT, the canals of teeth 11 and 21 were filled with photosensitizer methylene blue 0.005% for 5 min pre irradiation time (PIT) and irradiated by low power diode laser with visible red wavelength (660 nm) during 2 minutes without intervals, using an optical fiber delivering system with a helical movement from apical to cervical. Then the canals were filled with Ca(OH)2 paste for 45 days and had been changed each 15 days, and repeating the radiation. Results: After 45 days, the patient already had a bulging remission, with painless resistance to the apical pressure over the region and signs of bone repair confirmed with the radiographic examination, and total absence of signs or symptoms. Conclusion: The association of aPDT with Ca(OH)2 paste is effective in treating of periapical lesions of great extension and avoids surgical treatment.
Tratamento endodôntico de um grande cisto periapical com o auxílio de terapia fotodinâmica antimicrobiana: Relato de caso
Keywords: Antimicrobial; Calcium hydroxide; Diode Laser; Periapical cysts; Photodynamic Therapy; Root canal treatment